MEDB-79. MYC-driven upregulation of thede novo serine and glycine pathway is a novel therapeutic target for Group 3 MYC-amplified Medulloblastoma. (3rd June 2022) - Adiamah, Magretta; Lindsey, Janet C; Burté, Florence; Kohe, Sarah; Morcavallo, Alaide; Blair, Helen; Hill, Rebecca M; Singh, Mankaran; Crosier, Stephen; Zhang, Tong; Maddocks, Oliver; Peet, Andrew; et al.
Abstract: Despite advances in the molecular sub-classification and risk-stratification of medulloblastoma (MB), a subset of tumours remain refractory to current multimodal therapies. Group 3 (MBGroup3 ) patients represent around 25% of MBs, and amplification and elevated expression of MYC in this group correlates with dismal clinical outcomes. Since direct targeting of MYC remains elusive, understanding and exploiting metabolic dependencies in MYC-amplified MBGroup3 may reveal novel therapeutic opportunities. We engineered three independent regulable MYC -amplified MBGroup3 cell-based models, each harbouring doxycycline-inducible anti-MYC shRNAs (two independent species) or a non-silencing shRNA control. In all three models, MYC knockdown (KD) revealed persistent MYC-dependent cancer phenotypes, reduction in proliferation and cell cycle progression. We utilised 1 H high-resolution magic angle spectroscopy (HRMAS) and stable isotope-resolved metabolomics to assess changes in intracellular metabolites and pathway dynamics when MYC expression was modulated. Profiling revealed consistent MYC-dependent changes in metabolite concentrations across models. Notably, glycine was consistently accumulated following MYC KD suggesting altered pathway dynamics. 13 C-glucose tracing further revealed a reduction in glucose-derived serine and glycine ( de novo synthesis) following MYC KD which was attributable to lower expression of PHGDH, the rate-limiting enzyme of this pathway. Furthermore, in human primary tumours, elevated expression of PHGDH was associated with MYC amplification and poorer survival outcomes. MYC expressing cells showed greater sensitivity to pharmacological inhibition of PHGDH compared to MYC KD (MBGroup3 ) and MBSHH subgroup cell lines in vitro . Critically, targeting PHGDH in vivo, using MYC-dependent xenografts and genetically engineered mouse models, consistently slowed tumour progression and increased survival. In summary, metabolic profiling has uncovered MYC-dependent metabolic alterations and revealed the de novo serine/glycine synthesis pathway as a novel and clinically relevant therapeutic target in MYC -amplified MBGroup3 . Together, these findings reveal metabolic vulnerabilities of MYC -amplified MBGroup3 which represent novel therapeutic opportunities for this poor-prognosis disease group.